2022
DOI: 10.1039/d2cp00069e
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical library of N1s core binding energies of polynitrogen molecules and ions in the gas phase

Abstract: Polynitrogen molecules and ions are important building blocks of high energy density compounds(HEDCs). High energy bonds formed at the N sites can be effectively probed by the X-ray photoelectron spectroscopy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 70 publications
2
9
1
Order By: Relevance
“…Indeed, our calculated value is 0.22 eV lower than the experimental one (see Table 4). The DFT result of Chong and Hu 18 is only 0.11 eV lower, while that calculated by Du et al 19 differs by 0.45 eV. The condensed phase measurement result is lower by about 4 eV than our gas-phase value.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…Indeed, our calculated value is 0.22 eV lower than the experimental one (see Table 4). The DFT result of Chong and Hu 18 is only 0.11 eV lower, while that calculated by Du et al 19 differs by 0.45 eV. The condensed phase measurement result is lower by about 4 eV than our gas-phase value.…”
Section: Resultscontrasting
confidence: 84%
“…For comparison, the theoretical CEBEs have been calculated at the ΔM06-2X//mixed basis set level. These values and the results of other authors 17–19 are also shown in Table 4.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…DFT is the most efficient electronic structure method to model the core hole states and the core level binding energies. In the gas phase, the ΔKS approach has been validated to produce accurate absolute core IPs with a sub-electronvolt accuracy. The detailed number of mean absolute deviation (MAD) depends on the test sets, DFT functionals, and the edges. For instance, typically 0.5–1.0 eV was summarized by Bagus et al for IPs at different K-edges of light elements (C/N/O/F); 0.81 and 0.21 eV were reported by Pueyo Bellafont et al based on PBE and TPSS calculations for a test set of 68 molecules of light atoms (B/C/N/O/F 1s edges) or 0.3 eV by our group based on a test set of 20 molecules with the BP86 functional (N 1s edge only).…”
Section: Discussionmentioning
confidence: 99%
“…DFT usually can predict 1s binding energies with a sub-eV accuracy. The detailed value of the averaged deviation depends on test systems, functionals, and edges, for example, 0.3 eV 50 for some 20 molecules at the N 1s edge, or 0.5−1.0 eV 51 for several K-edges of light elements. In this work, we achieved excellent agreement with experiments in absolute BEs, with deviations of only 0.17, 0.15, and 0.09 eV for phenanthrene, coronene, and naphthalene.…”
Section: Structure Of the Core-ionized State Andmentioning
confidence: 99%